Development and design of a culturally tailored intervention to address COVID-19 disparities among Oregon's Latinx communities: A community case study - Budd, Elizabeth L.; McWhirter, Ellen Hawley; De Anda, Stephanie; Mauricio, Anne Marie; Mueller, Maryanne V.; Cioffi, Camille C.; Nash, Ashley; Van Brocklin, Kelsey; Yarris, Kristin; Jackson, Arriell; Terral, Heather; García, Jorge I. Ramírez; et al. (Frontiers in Public Health, 2022)
Background: Latinx communities are disproportionately affected by COVID-19 compared with non-Latinx White communities in Oregon and much of the United States. The COVID-19 pandemic presents a critical and urgent need to reach Latinx communities with innovative, culturally tailored outreach and health promotion interventions to reduce viral transmission and address disparities. The aims of this case study are to 1) outline the collaborative development of a culturally and trauma-informed COVID-19 preventive intervention for Latinx communities; 2) describe essential intervention elements; and 3) summarize strengths and lessons learned for future applications. Methods: Between June 2020 and January 2021, a multidisciplinary team of researchers and Latinx-serving partners engaged in the following intervention development activities: a scientific literature review, a survey of 67 Latinx residents attending public testing events, interviews with 13 leaders of community-based organizations serving Latinx residents, and bi-weekly consultations with the project’s Public Health and Community Services Team and a regional Community and Scientific Advisory Board. After launching the intervention in the field in February 2021, bi-weekly meetings with interventionists continuously informed minor iterative refinements through present day. Results: The resulting intervention, Promotores de Salud, includes outreach and brief health education. Bilingual, trauma-informed trainings and materials reflect the lived experiences, cultural values, needs, and concerns of Latinx communities. Interventionists (21 Promotores) were Latinx residents from nine Oregon counties where the intervention was delivered. Conclusions: Sharing development and intervention details with public health researchers and practitioners facilitates intervention uptake and replication to optimize the public health effect in Oregon’s Latinx communities and beyond.